An unprecedented case of cranial surgery in Longobard Italy (6th–8th century) using a cruciform incision - Micarelli, Ileana; Strani, Flavia; Bedecarrats, Samuel; Bernardini, Sara; Paine, Robert R.; Bliquez, Lawrence; Giostra, Caterina; Gazzaniga, Valentina; Tafuri, Mary Anne; Manzi, Giorgio (International journal of osteoarchaeology, 2023)
The Longobard necropolis of Castel Trosino dates from the 6th to the 8th century CE. Among the tombs excavated, the skull of an older female shows the first evidence of a cross‐shaped bone modification on a living subject. Macroscopic, microscopic, and CT scan analyses revealed signs of at least two sets of scraping marks. Specifically, SEM analysis shows that perimortem bone‐scraping traces are present on the skull. Both healed and non‐healed defects suggest that the woman has received at least twice intentional bone modifications to address her condition. This is the first evidence of a cross‐shaped therapeutic intervention on a living subject.